Reliability and Validity of Simplified Chinese Version of Roland-Morris Questionnaire in Evaluating Rural and Urban Patients with Low Back Pain - Yi, Honglei; Ji, Xinran; Wei, Xianzhao; Chen, Ziqiang; Wang, Xinhui; Zhu, Xiaodong; Zhang, Wei; Chen, Jiayu; Zhang, Diqing; Li, Ming (PLOS ONE, 2012)
Objective The causes of low back pain in China and Western countries are extremely different. We attempted to analyze the risk factors of low back pain in urban and rural patients under the dual economy with the simplified Chinese version of Roland-Morris disability questionnaire (SC-RMDQ) to demonstrate that SC-RMDQ could evaluate patients with low back pain arising from different causes. Methods Roland-Morris disability questionnaire was translated into SCRMDQ according to international guidelines for questionnaire adaptation. In this study, causes of low back pain of 187 outpatients and inpatients (99 urban patients and 88 rural patients) were analyzed. All patients underwent simplified Chinese version of Roland-Morris disability questionnaire (SC-RMDQ), simplified Chinese Oswestry disability index (SCODI) and visual analogue scale (VAS). Reliability was tested using reproducibility (intraclass coefficient of correlation – ICC) and internal consistency (Cronbach's alpha). Validity was tested using Pearson correlation analysis. Results The leading causes for low back pain were sedentariness (38.4%) and vibration (18.1%) in urban patients and waist bending (48.9%) and spraining (25%) in rural patients. Although causes of low back pain in the two groups of population were completely different, SCRMDQ had high internal consistency (Cronbach's α value of 0.874 in urban patients and 0.883 in rural patients) and good reproducibility (ICC value of .952 in urban patients and 0.949 in rural patients, P<0.01). SCRMDQ also showed significant correlation with Simplified Chinese version of Oswestry disability index (SCODI) and visual analogue scale (VAS) in rural areas (SCRMDQ-SCODI r = 0.841; SCRMDQ -VAS: r = 0.685, P<0.01) and in urban areas (SCRMDQ-SCODI: r = 0.818, P<0.01; SCRMDQ –VAS: r = 0.666, P<0.01). Conclusions Although causes of low back pain are completely different in rural and urban patients, SCRMDQ has a good reliability and validity, which is a reliable clinical method to evaluate disability of rural and urban patients.